Experimental investigations of the vortex-chain generated in the two-component plasma with the sheared flow of magnetized electrons - Chekh, Yu.; Goncharov, A.; Evsyukov, A. (Вопросы атомной науки и техники, 2006)
We present further experimental results on the observation of electron vortices in an electrostatic plasma lens at the strong radial gradient of electron density. Anharmonic low frequency large-amplitude potential waves propagating in azimuth direction are observed. The recently observed results give additional confirmation that the observed waves are the manifestation of the vortex-chain generated at the azimuthal sheared flow of magnetized electrons compensating ion beam.